Wind tunnel measurement iof aerodynamic characteristics of a generic eurocopter helicopter - Shuhaimi, Mansor, Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2012)
Link to publisher’s homepage at http://www.myiem.org.my/